The Effectiveness of the Disaster Resilient Village Program by the Local Disaster Management Agency - Rismawati Agusti; Andi Mulyadi; M. Rijal Amirulloh (Program Pascasarjana Universitas Negeri Makassar, 2023)
Disaster Resilient Village is a manifestation of the government's responsibility to provide protection to the community from the threat of disaster. The purpose of this research is to find out how effective the Disaster Resilient Village program by the Sukabumi City Regional Disaster Management Agency is. This research uses Duncan's theory. This research method uses qualitative research methods. Data collection techniques used observation, interviewing, and documentation techniques. Data validation methods used were source triangulation, technique triangulation, and time triangulation. The data analysis used is from Miles and Huberman, using data reduction, data presentation, and drawing conclusions and verification. The results of this study indicate that the Disaster Resilient Village program has been running in accordance with the established regulatory guidelines, but its implementation is still not running effectively, as there should be empowerment for the village to upgrade the criteria class of the village as stated in the Regulation of the Head of the National Disaster Management Agency Number 2 of 2012 regarding the implementation of the Disaster Resilient Village program, and the facilities and infrastructure are also not enough to maximize the workforce in supporting the Disaster Resilient Village program.